Caracterização Molecular e Funcional da Urease de Paracoccidioides brasiliensis - FERNANDES, Maria Regilda de Araújo (2009)
The pathogenic fungus Paracoccidioides brasiliensis is the etiologic agent of Paracoccidioidomycosis (PCM). The main route of contamination is the inhalation of fungal propagules that convert to yeast in the host tissues. The urease is among the factors of virulence described for dimorphic fungus. It hydrolyzes the urea producing molecules of ammonia and carbamate. Pbure has 3,012 bp, corresponding to a predicted protein of 837 amino acids, predicted molecular mass of 90 kDa and pI 6.0. PbURE has signature to nickel-dependent enzyme for its activity. The phylogenetic relationship between PbURE and urease from other fungi was evaluated. The cDNA that encodes PbURE was inserted into the expression vector pET-32a and recombinant protein of 103 kDa was expressed. Polyclonal antibody were produced against PbUREr and used on Western blot, Far-Western blot and ELISA. The results showed that PbUREr interferes on interaction between P. brasiliensis and pulmonary epithelial cells A549. PbUREr was able to bind to proteins fibronectin and type IV collagen, components of the extracellular matrix (ECM). The interaction between PbURE and calnexin protein was identified by the technique of two-hybrid.